2022
DOI: 10.3390/ijerph19063509
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Eight-Week Functional Core Training on Core Stability in Young Rhythmic Gymnasts: A Randomized Clinical Trial

Abstract: It is suggested that core stability (CS) might improve rhythmic gymnasts’ performance. Nevertheless, the effect of core stability training (CST) in CS performance is not clear. Purpose: Evaluating the effect of an eight-week functional CST on young rhythmics gymnasts’ CS performance. Method: A sample of 45 young female rhythmic gymnasts from a competitive team (age = 10.5 ± 1.8 years, height = 144.1 ± 10.6 cm, weight 38.2 ± 8.9 kg, peak height velocity (PHV) = 12.2 ± 0.6 years) participated in the study. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Reviewing the literature, we only found three works that studied the effects of CS training programs in a young rhythmic gymnast population. There were two studies mentioned earlier that showed an improvement in CS parameters and indicated that these improvements might enhance RG performance, although explosive strength was not measured [62,63]. The other RG study found significant improvements in the gymnasts' power, balance, and endurance after the CS training [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviewing the literature, we only found three works that studied the effects of CS training programs in a young rhythmic gymnast population. There were two studies mentioned earlier that showed an improvement in CS parameters and indicated that these improvements might enhance RG performance, although explosive strength was not measured [62,63]. The other RG study found significant improvements in the gymnasts' power, balance, and endurance after the CS training [45].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one prior study has analyzed the impact of an integrated CPT training program on rhythmic gymnasts [14], and one previous work has studied the CS training program's effect on rhythmic gymnasts' power [45]. Elsewhere, it has been suggested that CS training helps improve core performance, which might benefit RG performance [62,63,73]. Most available research has tried to demonstrate a relationship between PT and explosive strength performance in RG [36][37][38] and artistic gymnastics [59,60], while one study has assessed explosive strength after resistance training featuring strength and plyometrics exercises [66].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of several studies support those of this study. Trunk stability training has the potential to optimize the ability of the leg muscles to produce force, because it provides a stable base for the leg muscles to contract and it strengthens the neural drive [ 29 , 30 ]. Butcher et al reported that the improvement in the vertical takeoff speed after the three-week trunk stability training was due to changes in neuromuscular control or movement patterns rather than changes in muscle structure [ 6 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The WB-EMS+WBS group performed a specific training of the core and muscles on lumbar spine, as shown in Table 2 [50][51][52][53]. In total there were 12 WB-EMS sessions (20 minutes each with the same parameters as the other group) which were carried out over 8 weeks.In addition, the WB-EMS+WBS group performed a routine of 8 exercises on the WBS bench, immediately after the WB-EMS session (see Table 3 and Figure 4).…”
Section: Wb-ems+wbs Trainingmentioning
confidence: 99%
“…The WB-EMS + WBS group performed a specific training of the core and muscles on lumbar spine, as shown in ▶ Table 2 [50][51][52][53]. In total there were 12 WB-EMS sessions (20 minutes each with the same parameters as the other group) which were carried out over 8 weeks.…”
Section: Wb-ems + Wbs Trainingmentioning
confidence: 99%